Overtraining: Consequences and prevention - Eichner, E. R. (Journal of Sports Sciences, 1995)
Overtraining refers to prolonged fatigue and reduced performance despite increased training. Its roots include muscle damage, cytokine actions, the acute phase response, improper nutrition, mood disturbances, and diverse consequences of stress hormone responses. The clinical features are varied, non-specific, anecdotal and legion. No single test is diagnostic. The best treatment is prevention, which means (1) balancing training and rest, (2) monitoring mood, fatigue, symptoms and performance, (3) reducing distress and (4) ensuring optimal nutrition, especially total energy and carbohydrate intake.